Paradoksy potwierdzania a klauzula ceteris paribus - Grobler, Adam (Filozofia Nauki, 2013)
Well-known paradoxes of confirmation put the validity of inductive reasoning of any kind into question. Nevertheless, the proponents of hypothetical-deductive or abductive method make some use of inductivist motifs. If Popper is careful enough to distinguish between corroboration and confirmation, Lakatos quite straightforwardly maintains that falsification of one hypothesis is a confirmation of another. Next, Harman's reintroduction of abductivism long after Peirce's invention is, in fact, an attempt at grounding the inductive method in the principle of inference to the best explanation. In the paper, I claim that paradoxes of confirmation arise because of excessively formal analysis of scientific reasoning. It is commonly neglected that scientific hypotheses inevitably assume the ceteris paribus clause. Taking this into account gives the required solution to the paradoxes and sheds new light on the nature of inductive reasoning and its place in the scientific method.